Potential bioactivities via anticancer, antioxidant, and immunomodulatory properties of cultured mycelial enriched β-D-glucan polysaccharides from a novel fungus Ophiocordyceps sinensis OS8 - Chatnarin, Suwannachom; Thirabunyanon, Mongkol (Frontiers in Immunology, 2023)
Background Ophiocordyceps sinensis is well-known worldwide as a traditional medicine. An alternative natural source of O. sinensis is provided by mycelial cultivation. However, the bioactivities of cultured mycelial-enriched β-D-glucan polysaccharides from a novel fungus O. sinensis OS8 are still unknown. Methods We investigated the potential bioactivities via anticancer, antioxidant, and immunomodulatory polysaccharides (OS8P) produced from cultured mycelia of O. sinensis OS8. This strain is a novel fungus isolated from natural O. sinensis, which is further cultured by submerged mycelial cultivation for polysaccharide production. Results The yield of mycelial biomass was 23.61 g/l, and it contained 306.1 mg/100 g of adenosine and 3.22 g/100 g of polysaccharides. This OS8P was enriched with β-D-glucan at 56.92% and another form of α-D-glucan at 35.32%. The main components of OS8P were dodecamethyl pentasiloxane, 2,6-bis (methylthiomethyl) pyridine, 2-(4-pyrimidinyl)-1H-Benzimidazole, and 2-Chloro-4-(4-nitroanilino)-6-(O-toluidino)-1,3,5-triazine at the rates of 32.5, 20.0, 17.5, and 16.25%, respectively. The growth of colon cancer cells (HT-29) was significantly inhibited by OS8P, with IC50 value of 202.98 µg/ml, and encouraged apoptosis in HT-29 cells as confirmed by morphological change analysis via AO/PI and DAPI staining, DNA fragmentation, and scanning electron microscopic observations. In addition, significant antioxidant activity was demonstrated by OS8P through DPPH and ABTS assays, with IC50 values of 0.52 and 2.07 mg/ml, respectively. The OS8P also exhibited suitable immunomodulatory activities that significantly enhanced (P< 0.05) the induction of splenocyte proliferation. Conclusion The OS8P enriched with β-D-glucan polysaccharides and produced by submerged mycelial culture of a new fungal strain of O. sinensis OS8 strongly inhibited the proliferation of colon cancer cells without any cytotoxicity against normal cells. The potential effect of the OS8P on the cancer cells was due to the stimulation of apoptosis. Also, the OS8P exhibited good antioxidant and immunomodulatory activities. The results indicate that OS8P has promising applications in the functional food industry and/or therapeutic agents for colon cancer.